2007
DOI: 10.1093/nar/gkm001
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding mechanism revealed by high resolution crystal structure of Arabidopsis thaliana WRKY1 protein

Abstract: WRKY proteins, defined by the conserved WRKYGQK sequence, are comprised of a large superfamily of transcription factors identified specifically from the plant kingdom. This superfamily plays important roles in plant disease resistance, abiotic stress, senescence as well as in some developmental processes. In this study, the Arabidopsis WRKY1 was shown to be involved in the salicylic acid signaling pathway and partially dependent on NPR1; a C-terminal domain of WRKY1, AtWRKY1-C, was constructed for structural s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(140 citation statements)
references
References 53 publications
12
127
1
Order By: Relevance
“…For the longer C-terminal WRKY domain of WRKY4 or WRKY1 with more residues at the N terminus, there is actually another b-strand that is linked through a long bridging loop with the b-strand in which the WRKYGQK sequence is located (Duan et al, 2007). Asp-262 of the C-terminal WRKY domain of WRKY33 would be expected to be located in the C-terminal end of the long bridging loop (Duan et al, 2007).…”
Section: Vq Proteins As Group I and Iic Wrky-interacting Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the longer C-terminal WRKY domain of WRKY4 or WRKY1 with more residues at the N terminus, there is actually another b-strand that is linked through a long bridging loop with the b-strand in which the WRKYGQK sequence is located (Duan et al, 2007). Asp-262 of the C-terminal WRKY domain of WRKY33 would be expected to be located in the C-terminal end of the long bridging loop (Duan et al, 2007).…”
Section: Vq Proteins As Group I and Iic Wrky-interacting Proteinsmentioning
confidence: 99%
“…For the longer C-terminal WRKY domain of WRKY4 or WRKY1 with more residues at the N terminus, there is actually another b-strand that is linked through a long bridging loop with the b-strand in which the WRKYGQK sequence is located (Duan et al, 2007). Asp-262 of the C-terminal WRKY domain of WRKY33 would be expected to be located in the C-terminal end of the long bridging loop (Duan et al, 2007). Asp-262 of WRKY33 is also adjacent to the highly conserved Asp-263, which forms a salt bridge with the Trp residue in the invariant WRKYGQK sequence (Duan et al, 2007), which, in turn, is adjacently connected with the first Cys residue of the zinc-finger motif (Yamasaki et al, 2012).…”
Section: Vq Proteins As Group I and Iic Wrky-interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wRKY signature sequence enters the major groove of DNA and binds to its cognate DNA-binding site (TTGACC/T) known as the w box (Yamasaki et al 2005). A few years later, a crystal structure description of the AtwRKY1 C terminal wRKY domain showed a similar structure (Duan et al 2007). Recently, another major advance was made with the first reporting of the solution structure of a wRKY domain in complex with the w box binding site (Yamasaki et al 2013).…”
Section: Wrky Transcription Factors-domain Structure and Bindingmentioning
confidence: 99%
“…Although an Ala scanning study showed that mutation of the Q residue had only a minor effect on binding of NtWRKY9 to the consensus W box (Maeo et al, 2001), NMR spectroscopy measurements have revealed that the Q residue is one of the four amino acids in the WRKYGQK sequence of AtWRKY4 that contacts the bases in the major groove of the DNA and therefore is highly significant for sequencespecific recognition (Yamasaki et al, 2005). Recently, an extensive mutational analysis of the region containing the C-terminal WRKY domain of AtWRKY1 confirmed that the Q to K mutation affected its binding to the consensus W box (Duan et al, 2007). NtWRKY12 mutant proteins in which the GKK sequence was changed to GQK or GEK (another WRKY domain sequence variation occurring, for example, in WRKY proteins of rice) were not able to bind to either the WK box-containing Blm-m1 probe or the Blm-m10 probe with the consensus W box (Fig.…”
Section: Ntwrky12 Contains a Variant Wrky Domainmentioning
confidence: 99%